Wawasan Al-Qur’an tentang Mental Health, Studi Al-Qur’an Tematik dengan Pendekatan Grounded Theory - Annida Nazirah; Nadia Nurpadilah; Hanifatul Azizah; Muhammad Alif (STIKes Ibnu Sina Ajibarang, 2025)
This research seeks to examine the teachings of the Qur'an thematic perspectives on mental health using a grounded theory approach. Even though the phrase